LAW ENFORCEMENT EFFECTIVENESS AGAINST DIGITAL CONTENT PIRACY IN THE PERSPECTIVE OF INTELLECTUAL PROPERTY LAW - Hermanto (PT. Radja Intercontinental Publishing, 2026)
The rapid development of digital technology has significantly expanded the distribution of copyrighted works, however it has also intensified the practice of digital content piracy, resulting in economic losses and weakening legal protection for copyright holders. This condition highlights the urgency of examining the effectiveness of the existing legal framework. This study aims to analyze the effectiveness of law enforcement against digital content piracy from the perspective of intellectual property law, focusing on normative consistency, regulatory harmonization, and the adequacy of legal sanctions. The research employs a normative legal method with statutory and conceptual approaches, utilizing primary legal materials including Law Number 28 of 2014 on Copyright, Law Number 11 of 2008 concerning Electronic Information and Transactions as amended by Law Number 19 of 2016, Government Regulation Number 71 of 2019, and Minister of Communication and Informatics Regulation Number 5 of 2020 as amended by Regulation Number 10 of 2021. These materials are analyzed using qualitative descriptive analytical methods. The findings indicate that normatively the legal framework governing digital content piracy is relatively comprehensive, however there remain regulatory inconsistencies, weaknesses in sanction formulation, and limitations in addressing the dynamics of digital platforms which may hinder effective law enforcement. The novelty of this research lies in its integrated cross regulatory analysis to identify normative gaps within the digital copyright protection regime. This study concludes that regulatory harmonization, strengthening of sanction norms, and legal policy reform are necessary to enhance the effectiveness of intellectual property protection in the digital era.